High ambient air pollution erodes the benefits of using clean cooking fuel in preventing low birth weight in India - Ritu Parchure; Ekta Chaudhary; Shrinivas Darak; Santu Ghosh; Alok Kumar; Sagnik Dey (Environmental Research Letters, 2024)
A large fraction of the population in rural India continues to use biomass fuel for cooking and heating. In-utero exposure to the resulting household air pollution (HAP), is known to increase the risk of low birth weight (LBW). Mitigating HAP, by shifting to clean cooking fuel (CCF), is expected to minimize the risk associated with LBW. However, India also has high levels of ambient air pollution (AAP). Whether exposure to AAP modifies the effect of reducing HAP by switching to CCF on LBW is not known. The present study addressed this knowledge gap by analyzing the National Family Health Survey (2019–21) data of the most recent full-term, singleton, live births from rural households born after 2017 ( n = 56 000). In-utero exposure to AAP was calculated from satellite-derived ambient fine particulate matter (PM _2.5 ) concentration at the level of the primary sampling unit for the pregnancy duration of the mothers. The moderation by ambient PM _2.5 level on the odds of LBW among CCF users was examined by logistic regression analysis with interaction. The adjusted odds ratio (aOR) of LBW was 7% lower among users of CCF. At the lowest Decile (20–37 μ g m ^−3 ) of ambient PM _2.5 exposure, the aOR of LBW among CCF users was 0.83 (95% CI:0.81–0.85). At every 10th percentile increase in ambient PM _2.5 exposure (in the range 21–144 μ g m ^−3 ), aOR increased gradually, reaching the value of 1 at PM _2.5 level of 93 μ g m ^−3 . Our results, therefore, suggest that the benefit of using CCF during pregnancy may be downgraded by moderate to high ambient PM _2.5 exposure.